A new genus of egg case-carrying water scavenger beetle from the Guiana Shield (Coleoptera: Hydrophilidae: Acidocerinae) - Short, Andrew Edward Z.; García, Mauricio (Zootaxa, 2014)
Radicitus gen. n. is described to accommodate three new species of water scavenger beetles from the Guiana Shield region of South America: R. ayacucho sp. n. (Venezuela), R. granitum sp. n. (Venezuela), and R. surinamensis sp. n. (Suriname). The genus is placed in the subfamily Acidocerinae, and likely shares an affinity with the genus Helochares Mulsant and its relatives. It is characterized by its convex body form, short maxillary palps, partially glabrous hind femora, and complete fifth abdominal ventrite. All collections of the new genus were made from root mats and debris from seepages over rock outcrops or, rarely, root mats from streams. Individual females of all three species were observed to adhere their egg case to the venter of the abdomen.